A Randomized, Double‐blind, Placebo‐controlled Trial to Evaluate the Efficacy and Safety of Pregabalin for Postherpetic Neuralgia in a Population of Chinese Patients. Issue 1 (30th December 2015) - Liu, Quanzhong; Chen, Haibo; Xi, Liyan; Hong, Zhen; He, Li; Fu, Yi; Fang, Hong; Shang, Ningxiu; Yan, Ping; Fan, Dongsheng
Abstract: Background and purpose: Currently, there are limited options for treatment of postherpetic neuralgia (PHN) patients in China. While pregabalin is an effective treatment option for PHN in several countries, there is limited information on its efficacy in Chinese patients. Methods: This was an 8‐week, double‐blind, placebo‐controlled trial in Chinese patients with PHN randomized (1:1) to pregabalin 300 mg/day or placebo. Primary efficacy endpoint was change from baseline in mean pain score (Daily Pain Rating Scale; 0 = 'no pain' to 10 = 'worst possible pain'). Secondary efficacy endpoints included change from baseline in overall pain intensity score, by visual analog scale (VAS; 0 = 'no pain' to 100 = 'worst possible pain') and daily sleep interference score (0 = 'pain does not interfere with sleep' to 10 = 'completely interferes'). Results: A total of 220 patients were randomized and received treatment (111 pregabalin and 109 placebo). Improvement in mean pain score with pregabalin was significantly greater than placebo, least squares mean difference (95% CI), −0.71 (−1.08, −0.34); P = 0.0002. Improvements in VAS and sleep interference score at endpoint were significantly greater with pregabalin than placebo, least squares mean difference (95% CI), −8.18 (−11.99, −4.37); P < 0.0001, and −0.54 (−0.93, −0.14); P = 0.0079, respectively. Adverse events were consistent with current product labeling, with dizziness the most commonly reported adverse event (24.3% of pregabalin‐treated patients). Conclusion: Pregabalin improved measures of pain and sleep, and is well tolerated in Chinese patients with PHN. These results may inform physicians treating patients with PHN in China.